The Effects of Digitalization on Mothers’ Decision to Engage in Entrepreneurship: An Analysis of the 2022 Susenas Data - Muhammad Dzaky Rafliansyah; Pratomo, Devanto Shasta (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
Recently, a lot of mothers in Indonesia enter the labor market as entrepreneurs. Mothers’ entry in labor market marks mothers’ needs to help family’s economy. Internet is supposed to help them to enter entrepreneurship world. However, to date, there is minimal literature that discuss role of internet to mother’s decision as an entrepreneur, making its specific role is being questioned in this research. Thus, this research is done to answer that question by analyzing impact of internet usage on mother’s chance to become as an entrepreneur. Method used is binary logistic regression with Susenas Maret 2022 as data source. Hopefully, this research becomes justification of the importance of mothers’ empowerment.